Cardioneuroablation for Vasovagal Syncope: An Updated Systematic Review and Single-Arm Meta-Analysis - Alexandru Ababei; Cosmin Gabriel Ursu; Mircea Ioan Alexandru Bistriceanu; Darie Ioan Andreescu; Iasmina-Maria Iurea; Beatrice Budeanu; Adriana Elena Dumitrache; Alexandra Hostiuc; Maria-Celina Sturz-Lazar; Cristian-Valentin Toma; Stefan Sebastian Busnatu; Alexandru Deaconu; et al. (Biomedicines)
Background: When conservative therapies are insufficient for vasovagal syncope (VVS), procedural options such as permanent pacemakers or catheter ablation of ganglionated plexi (GP) may be considered. This meta-analysis aimed to evaluate the efficacy of GP catheter ablation in patients with VVS. Methods: A comprehensive literature search was performed in PubMed, Embase, and the Cochrane Library from 15 March 2024 to 10 May 2025. After duplicate removal, two reviewers independently screened studies and assessed full texts based on predefined criteria. A single-arm proportion meta-analysis was conducted. Results: Thirty-seven studies comprising 1585 participants were included. The pooled proportion of VVS recurrence after ablation was 8.9% (95% CI, 6.4–11.4%), but with substantial heterogeneity (I2 = 74.4%, p < 0.001). Sensitivity and subgroup analyses confirmed the robustness of the pooled estimate. A meta-regression was performed to further explore potential effect modifiers, but no covariate reached statistical significance. Conclusions: This meta-analysis suggests that ganglionated plexi catheter ablation may be associated with a reduced recurrence of vasovagal syncope in selected populations. However, the findings are based predominantly on non-randomized observational studies, and the high between-study heterogeneity limits the strength of inference. Future randomized controlled trials with standardized methodologies are needed to confirm the long-term efficacy and safety of this intervention.